Processing of crude palm oil with ceramic microfiltration membrane - Majid, Rusnani Abd.; Baharin, Badlishah Sham; Ahmadun, Fakhru'l-Razi; Che Man, Yaakob B. (Blackwell Publishing Inc, 2000)
Membrane separation technology offers a potential application in the processing of crude palm oil. Ceramic membranes with different pore diameters (0.45 and 0.2 micron) were used to conduct the study on micromembrane process. Quality parameters of membrane-processed oils examined included free fatty acid (FFA), carotene, fatty acid composition (FAC), phosphorus and iron contents. The effect of operating parameters such as transmembrane pressure, feed flow and time on permeate flux were evaluated. It was found that 'Ceraflo' ceramic membrane with a pore size of 0.4 5 micron was only able to reject 14% of phosphorus from the crude oil. Ceramic membrane with pore size of 0.2 micron showed a better phosphorus rejection of 56.8%. The permeate was found to contain 7.13 ppm of phosphorus. The 0.2 micron membrane was also able to remove more than 80% of the iron from crude palm oil. Pore sizes for both membranes were not small enough to remove other components such as FFA, and carotene. Both membranes showed a similar trend in which the permeate flux increased with transmembrane pressure and feed flow until a certain limit where the flux declined with increasing pressure and feed flow. The limits in transmembrane pressures for membrane with pore sizes of 0.45 and 0.2 micron were 1.65 and 1.25 bar, respectively. Whereas the limits in feed flow for 0.45 micron and 0.2 micron membranes were 9.2 and 9.8 L/min, respectively. The flux decline of filtered oil through 'Ceraflo' ceramic membrane was rapid, but found to be quite stable for the period of 5 h of processing after an initial decline.